G155(P) Audit of anaphylaxis management in an NHS trust: are we following national guidance. (May 2019) - Seager, E; Dhesi, A; Raptaki, M; Makwana, N; Atkinson, M; Karanam, S; Ivanova, A; North, J
Abstract : Aim: Anaphylaxis is an acute systemic reaction which can be life-threatening. Our aim was to evaluate the compliance of our trust with national guidance. Method: We performed a retrospective analysis of all children aged 0–16 years, with a coded diagnosis of anaphylaxis in our trust from 2014 to 2016. A proforma was compiled and data was collected from clinical records. Results: 49 clinical records were available. 28/49 were considered to have true anaphylaxis. Median age was 11 years. Presenting symptoms were pharyngeal/laryngeal oedema (79%), bronchospasm with tachypnoea (82%), circulatory collapse (4%) and skin/mucosal changes (100%). All had the preceding causative circumstances documented and time of onset of symptoms. The suspected triggers were: nuts (61%), sesame (7%), jackfruit (3.5%), amoxicillin (3.5%), ibuprofen (3.5%) and wheat-dependent exercise-induced anaphylaxis (3.5%). In 18% the exact culprit was unclear or unknown. 50% of patients had a previous history of anaphylactic reaction. 75% received intramuscular (IM) adrenaline with half of these being given pre-hospital. 46% received nebulised salbutamol, 89% antihistamine and 89% steroids. At discharge, in 89% an allergy clinic was planned, 68% had an IM adrenaline auto-injector of which 84% had auto-injector training. Emergency action information in case of anaphylaxis was provided to 68% along with leaflet/written emergency plan in 11%. Information regarding warning signs/symptoms was documented in 61% and where a causative trigger was identified, 48% received avoidance advice. 11% had information regarding the risk of a biphasic reaction but nobody was informed about support groups. Conclusion: The diagnosis of 'severe allergic' reaction rather than anaphylaxis, may explain why only 75% patients received IM adrenaline. This has however increased compared to an audit performed in our trust from 2002 to 2006 where IM adrenaline was administered to just 57%. Since then, implementation of local guidance may explain the improvement. Interestingly, 37.5% of patients with no airway/breathing/circulation symptoms received adrenaline, highlighting the need for ongoing education. This audit shows good history taking and examination but emphasis needs to be placed on counselling and written emergency plans on discharge. This can then be reinforced at allergy clinic.